The initial formation of teachers in scholastic cartography: a report on a research experience - Cabral, Marcia Pereira [UNESP]; Castreghini de Freitas, Maria Isabel [UNESP] (Iated-int Assoc Technology Education A& Development, 2012)
This paper is derived from the PhD research entitled "The initial training of Geography teacher in school cartography: a reflective analysis", developed by the program of Post-graduation in Geography of UNESP, campus of Rio Claro. The research is in the final phase, focused on data analysis and final writing of thesis. In this context, it may be stated that the research orientates in the problematic focused at the understanding of how the recent knowledge produced by the school cartography unfolds in the practices of Geography licentiate students. However, at this time, we will discuss about issues related to the research by the theoretical and practical point of view.
Keywords: Scholastic Cartography; Initial Formation of Teachers; Research Experience